Improving Tc in sodalite-like boron-nitrogen compound M2(BN)6. (July 2022) - Hai, Yu-Long; Tian, Hui-Li; Jiang, Meng-Jing; Li, Wen-Jie; Zhong, Guo-Hua; Yang, Chun-Lei; Chen, Xiao-Jia; Lin, Hai-Qing
Abstract: To explore the improvement of the critical temperature ( T c ) of boron-nitrogen materials, the doping effect of other elements into the sodalite-like clathrate compounds M 2 (BN)6 is studied, based on the first-principles calculations. The stability, electronic structures, dynamical properties, and electron-phonon coupling interactions of these materials upon doping suggest that they are potential high-temperature superconductors. The result shows that the highest T c of boron-nitrogen clathrate compound at ambient pressure reaches 72 K by doping Al. Boron-nitrogen clathrates doped by H, In, Tl, Si, and Ge also possess the high T c values of 45, 54, 67, 58, and 41 K at ambient pressure, respectively. By increasing the doping concentration, the T c value of boron-nitrogen clathrate can be obviously improved and nearly doubled. The predicted T c of 72 K is the highest value for all boron-nitrogen materials at ambient pressure. It is much higher than those of magnesium diboride and alkali fullerides. Graphical abstract: Image 1 Highlights: T c is improved in boron-nitrogen clathrate compound by increasing dopant content. T c ∼72 K of Al2 (BN)6 is the highest record among all boron-nitrogen materials at ambient pressure. M 2 (BN)6 is predicted as the potential high-temperature superconductor stabilizing at ambient pressure.